2012
DOI: 10.1137/110837486
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary Learning for Noisy and Incomplete Hyperspectral Images

Abstract: We consider analysis of noisy and incomplete hyperspectral imagery, with the objective of removing the noise and inferring the missing data. The noise statistics may be wavelength-dependent, and the fraction of data missing (at random) may be substantial, including potentially entire bands, offering the potential to significantly reduce the quantity of data that need be measured. To achieve this objective, the imagery is divided into contiguous three-dimensional (3D) spatio-spectral blocks, of spatial dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 37 publications
(62 reference statements)
0
109
0
Order By: Relevance
“…DL has also been investigated to restore HS images [34]. More precisely, a Bayesian scheme was introduced in [34] to learn a dictionary from an HS image, which imposes a self-consistency of the dictionary by using Beta-Bernoulli processes. This Monte Carlo-based method provided interesting results at the price of a high computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…DL has also been investigated to restore HS images [34]. More precisely, a Bayesian scheme was introduced in [34] to learn a dictionary from an HS image, which imposes a self-consistency of the dictionary by using Beta-Bernoulli processes. This Monte Carlo-based method provided interesting results at the price of a high computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…However, here we are considering diverse spectral patterns over several wavelengths, and devising a similarly appropriate scheme is beyond the scope of this paper. In fact, in previous work on denoising and inpainting of hyperspectral images [32], it has been observed that BPFA outperformed KSVD significantly. Furthermore, there is a lot of difference in the manner in which sparse codes are updated in KSVD and BPFA.…”
Section: Hf-psnr and Ssim Values Are All Presented Inmentioning
confidence: 95%
“…Beta process factor analysis (BPFA) is a non-parametric Bayesian dictionary learning technique that has been applied for denoising and inpainting of grayscale and RGB images [27], and it has also been utilized for inpainting hyperspectral images [32] with substantial missing data. The beta process is coupled with a Bernoulli process, to impose explicit sparseness on the coefficients {c i } i=1,N .…”
Section: A Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…CS approaches have been shown to reduce dose by as much as 90% in electron microscopy [2,3,4]. Optical imaging and microscopy have also seen substantial benefits [5,6,7,8,9,10,11,12,13]. This tutorial will briefly introduce the principles of CS.…”
mentioning
confidence: 99%